รำตรวจพลวิรุญจำบัง - เนียมคำ, สุรเดช (Academic Journal Phranakhon Rajabhat University, 2017)
The purposes of research were to study 1) the history and the role of the charater through time. Moreover, to observe the dance patterns of Wirunchambung who uses the spear as his weapon. 2) The troop reviewing dance will study especially in Wirunchambung’s strategies of using his spear. 3) The research method applied in this study was qualitative. The population 5 person was giant khon the instuments for collecting data were in – depth interview fogus group discussion and brain stoming.The data were analyzed by content analysis and presented in descriptive. The results found 1) Wirunchambung’s history from the old capital literature had mentioned Wirunchambung only in the procession of horse troops of the narration of Ramakian. For Thonburi literature, it had added up the role and the importance of Wirunchambung by brought the magical and the spells to fight with Hanuman. In Rattanakosin issue had mentioned Wirunchambung as the person who loved in his clan and his friends. In addition his characteristic was a range person. He is a gallant person, but honorable to women. 2) For a study, the dancing patterns with the spear that was used by Wirunchambung. It could analyze the dancing pattern step by step of the troops reviewing. There are six different parts of the performance. 1. It is the opening scene it reflected the elegance of both the performer and the weapon. 2. The performer expressed the strength and skillful in swinging, throwing and catching the weapon according to rhythm of the music. 3. The dance pattern was lead to the accuracy for the right rhythm, the position on the stage and also the relationship of both feet and hands. 4. The dance pattern displayed the unique patterns of using the spear. 5. The dance was telling the tradition pattern of soothing the army and preparing the troops. 6. In the middle space of the stage the dance distributed the majestic horse riding with the spear in order to control the horse. 3) The strategies of using the spear while Wirunchambung reviewing the troops. There are consisted of 16 dance pattern (1) One hand holding the spear by pointing the blade upward position. (2) Holding the spear by raising position. (3) Swirling the spear with one hand by holding at almost at blade of the spear. (4) Swirling the spear with one hand in the middle of the spear. (5) Holding the spear in downward position. (6) Holding the spear in a position of trample and thrash. (7) Raising the spear in a certain level. (8) Throwing the spear. (9) Moving the spear (10) Display the spear in order to ostentatious. (11) Flipping the spear and point the blade down. (12) Protecting the spear with a fast movement. (13) The movement of keeping the weapon in a certain position. (14) Tha Tue Hock Song Mue Ten Pa Teng Pa) Holding the spear with both hands along with the dance pattern of pa teng pa. (15) The pattern of the horse whipping with the spear. (16) Swaying the horse.